Can we tackle climate change by behavioral hacking of the dopaminergic system? - Munuera, Jérôme; Burguière, Eric (Frontiers in Behavioral Neuroscience, 2022)
Climate change is an undeniable fact that will certainly affect millions of people in the following decades. Despite this danger threatening our economies, well-being and our lives in general, there is a lack of immediate response at both the institutional and individual level. How can it be that the human brain cannot interpret this threat and act against it to avoid the immense negative consequences that may ensue? Here we argue that this paradox could be explained by the fact that some key brain mechanisms are potentially poorly tuned to take action against a threat that would take full effect only in the long-term. We present neuro-behavioral evidence in favor of this proposal and discuss the role of the dopaminergic (DA) system in learning accurate prediction of the value of an outcome, and its consequences regarding the climate issue. We discuss how this system discounts the value of delayed outcomes and, consequently, does not favor action against the climate crisis. Finally, according to this framework, we suggest that this view may be reconsidered and, on the contrary, that the DA reinforcement learning system could be a powerful ally if adapted to short-term incentives which promote climate-friendly behaviors. Additionally, the DA system interacts with multiple brain systems, in particular those related to higher cognitive functions, which can adjust its functions depending on psychological, social, or other complex contextual information. Thus, we propose several generic action plans that could help to hack these neuro-behavioral processes to promote climate-friendly actions.